Universal salt iodization potentially contributes to health equity: socio-economic status of children does not affect iodine status - Milevska-Kostova, Neda; Miladinova, Daniela; Kuzmanovska, Sonja; Majstorov, Venjamin; Ittermann, Till; Völzke, Henry (Walter de Gruyter GmbH, 2022)
Many studies have shown that socio-economic status (SES) contributes to health inequalities, with nutrition as one of the major risk factors. Iodine intake entirely depends on external sources, and deficiencies are known to be more prevalent in lower social groups, especially in countries with limited access to iodized salt. This study aimed to determine the influence of SES on iodine status and iodine availability from household salt in North Macedonia.